Memahami Landasan Teologis Dalam Pendidikan Agama Kristen - Walde Mesah; Yundri Mesah; Sandra Rosiana Tapilaha (International Forum of Researchers and Lecturers, 2024)
This article discusses the theological foundations of Christian religious education, which not only includes understanding religious concepts, but also shapes a person's character and spirituality. This theological foundation is strengthened by biblical principles, where Christian religious teachings are seen as an important mission based on the great mission of the Lord Jesus in Matthew 28:19-20. This foundation places the Bible as the highest authority and main source of truth and elevates the character of Jesus Christ as the main example. understand the theological basis of Christian religious teachings. The research results show that the aim of Christian religious education is to develop human potential according to the teachings of the Bible, with a focus on developing character, values ​​and spirituality according to the teachings of Christ. The Bible is considered. the highest authority in all areas of life, including Christian education, and is the basis of Christian religious education. The character of Jesus Christ who was caring, merciful, humble and lived a simple life is an example for Christians in their daily lives. Moreover, this article also helps develop individual spirituality. The teachings of Christianity, whose main focus is awareness of a transcendent relationship with God. The role of the Holy Spirit is also considered important to strengthen understanding of Bible teachings and guide Christians to live according to God's will.